2020
DOI: 10.5539/elt.v13n6p144
|View full text |Cite
|
Sign up to set email alerts
|

Is it Worth Flipping? The Impact of Flipped Classroom on EFL Students’ Grammar

Abstract: In light of contemporary pedagogical methods, the flipped classroom has been recognised as an effective pedagogy in English as a Foreign Language (EFL). This study employed a quasi-experimental one-group research design to investigate the impact of flipped learning on Omani EFL learners’ grammar and to examine students’ perceptions on the flipped classroom. An intact group of students (n=28) enrolled at the foundation programme in Arab Open University-Oman was randomly selected. Seven video… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
3
11
0
1
Order By: Relevance
“…Moreover, all previous studies of the flipped classroom approach for nursing education have been conducted in the United States or Europe, where the language of instruction at the university level is the same as in secondary schools. Studies examining the efficiency of the flipped classroom approach in Oman have been scarce and limited mainly to English language teaching [ 18 20 ]. Therefore, the aim of this study was to determine the impact of flipping one A&P chapter on performance and satisfaction of Omani nursing students.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, all previous studies of the flipped classroom approach for nursing education have been conducted in the United States or Europe, where the language of instruction at the university level is the same as in secondary schools. Studies examining the efficiency of the flipped classroom approach in Oman have been scarce and limited mainly to English language teaching [ 18 20 ]. Therefore, the aim of this study was to determine the impact of flipping one A&P chapter on performance and satisfaction of Omani nursing students.…”
Section: Introductionmentioning
confidence: 99%
“…The researcher concluded that flipped instruction could assist the students in becoming active learners in class. Regarding other Arab countries, Flipped classrooms have also been implemented in Oman (Al-Naabi, 2020). In this study, 25 participants (EFL students) from an Omani university were involved where flipped classroom method was adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the study was limited to students from a single Omani university. This study also proposed that teachers should create brief videos that are easy for learners to comprehend and follow (Al-Naabi, 2020). Since the main goal is to make online availability of lessons to students and to allow students to view them at their own pace and level of understanding, the flipped classroom can serve this role excellently.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Naabi, I.S. (2020) [42] Investigating the impact of flipped learning on Omani EFL learners' grammar and examining students' perceptions of the flipped classroom.…”
Section: Quantitative 384mentioning
confidence: 99%